FORMULATION, CHARACTERISATION AND OPTIMISATION OF NATURAL ARGAN OIL MICROEMULSION FOR TOPICAL DELIVERY - OUHADDOUCH, HIND; ALIAT, ZINEB; LAATIRIS, ABDELKADER; CHERKAOUI, NAWAL; FAHRY, AICHA; RAHALI, YOUNES; EL ALAOUI, YASSIR (International Journal of Applied Pharmaceutics, 2025)
Objective: The purpose of this study was to develop, optimize and characterize a stable microemulsion of Moroccan cosmetic Argan oil. Methods: In this work, microemulsion system was studied by the construction of phase diagrams using titration method. At first, various surfactants (Brij56®, Tween 80®, Solutol®, Tween 20® and Labrasol®) and various weight ratio surfactant/cosurfactant (1:0, 3:1, 2:1 and 1:1) were tested to select the optimal surfactant and concentration to use. The microemulsions with tween80 were evaluated with different techniques using various parameters such as droplet size, transmittance, viscosity and pH. Stability studies of these microemulsions were conducted for 8 w at 5 °C, 25 °C and 40 °C, and underwent centrifugation at 3000 rpm and ultracentrifugation at 10,000 rpm. Results: The largest microemulsion formation area was achieved for the microemulsions containing Tween 80/PEG 400 at a ratio of 3:1. The obtained microemulsions M1 to M12 were homogeneous. More the percentage of PEG 400 increases, more the pH of the preparations and their viscosity decreases, while preparations with a high oil content have low transmittance. Thermodynamic and physical stability shows that only samples with a minimum of 31.5% of Tween 80 and a maximum of 9% of oil showed good stability. Among the stable preparations, M11 (9% O, 10% W and 40.5/40.5% S/Cos) was the formula which exhibited properties such as transparency, soft acidic pH and low viscosity, making it suitable for cutaneous use. Conclusion: The use of pseudo-ternary phase diagrams allows for the development of an optimal microemulsion with perfect stability.